Electronic publication in zoological nomenclature and taxonomy: problems, responses and solutions - Zhang, Zhi-Qiang (Zootaxa, 2014)
In September 2012, the International Commission on Zoological Nomenclature (ICZN 2012) published an amendment of Articles 8, 9, 10, 21 and 78 of the International Code of Zoological Nomenclature (ICZN 1999) to allow electronic publication in zoological nomenclature and taxonomy (see also Zhang 2012). Late last year, a paper in Zootaxa (Dubois et al. 2013) reviewed some of the problems related to electronic publication of zoological nomenclature and taxonomy, and in turn evoked rapid reactions from Nature (Anonymous 2013) and BMC (Harold et al. 2013). This issue of Zootaxa contains a response to Dubois et al. (2013) from the International Commission on Zoological Nomenclature (ICZN 2014), and a formal response from the editors of BMC (Moylan et al. 2014). Zootaxa is pleased to provide a forum for discussions of this type, and encourages debate on issues important in zoological nomenclature and taxonomy (Zhang 2007).